The Reality of the Criminal Justice System in Independence of Law Enforcement Based on Pancasila Law System - Lindu Aji Saputro; Siti Rodhiyah Dwi Istinah; Siti Ummu Adillah (Law Development Journal, 2022)
The purpose of this research is to find out how is the Independence of the Criminal Justice System by the law enforcement sub-system and how is the Reconstruction of the Independence of the Criminal Justice System. This research approach uses normative juridical. Based on the research, it is concluded that the independence of the National Police mainly lies in the implementation of "police discretion", which unfortunately has not been adequately accommodated in the provisions of the applicable laws and regulations. This resulted in the face of the Police solely as an organization whose main task is to protect and serve the community. Meanwhile, the performance of the National Police as an effective, efficient, fast and measurable crime eradication organization has not been accommodated in the existing police regulations.